¿Qué hay de nuevo, viejo? Reflexiones sobre la anhelada ciudad justa - Guevara-Cue, Gabriela (2025)
The essay advocates for a critical reassessment of the concepts of the right to the city, spatial justice, and the just city within the current urban planning paradigm. It emphasizes the interplay between theoretical frameworks and the foundations for social action grounded in spatiality, identifying key challenges in operationalizing the concept of a just city, such as the ambiguity of the term, the complexity of multiscalar governance, and the necessity to define common objectives. The essay stresses the importance of establishing a robust and sustainable science-policy interface to progress toward a just city. Furthermore, it highlights the need to transcend isolated planning actions to critically examine the underlying ideological and epistemological foundations, as well as the power structures that perpetuate inequalities and injustices particularly in Latin America. This includes the implementation of policies that promote equity and spatial justice, alongside a reflection on the frameworks of domination embedded in urban space.